Collaborative analysis on differences in volatile compounds of Harbin red sausages smoked with different types of woodchips based on gas chromatography–mass spectrometry combined with electronic nose. (May 2021) - Yin, Xiaoyu; Wen, Rongxin; Sun, Fangda; Wang, Yan; Kong, Baohua; Chen, Qian
Abstract: In this study, the volatile profiles of Harbin red sausages smoked with pear, oak, apple and beech woodchips were evaluated using the combination of solid-phase microextraction gas chromatography-mass spectrometry (SPME-GC/MS) and electronic nose (E-nose). Comparisons of the colour, texture profile and sensory attributes were also conducted. The E-nose data and GC/MS data were analysed by principal component analysis (PCA), respectively. The correlation between E-nose sensor responses and volatile compounds was evaluated with partial least squares regression (PLSR). The results showed that the smoking process played an important role in the formation of volatile compounds of Harbin red sausage. The smoking process caused an increase in the intensity of smoky odour, and the sausage smoked with different woodchips showed higher smoky odour compared with the unsmoked sausage ( P < 0.05). A total of 87 volatile compounds were identified by GC/MS. According to the odour activity values, the characteristic odour of the Harbin red sausages mainly resulted from 22 volatile compounds. PCA of the volatile compounds and E-nose sensors could effectively differentiate sausages that were unsmoked and separately smoked with different woodchips. Furthermore, the PLSR results ( P < 0.05, Q 2 = 0.619) indicated that there was a high correlation between the E-nose sensors and volatile compounds. Highlights: A total of 87 volatiles were identified in sausages smoked with different woodchips. Phenols were the most abundant class of volatile compounds in the smoked sausages. Twenty-two volatiles with OAV>1 were the major contributors to unique flavour. The E-nose and GC/MS system could effectively differentiate the smoked sausages. The W1S, W1W, W2S and W2W sensors exhibited strong correlation with volatiles.